Anesthesia recovery comparison between remifentanil-propofol and remifentanil-desflurane guided by Bispectral Index® monitoring - Rocha,Raphael Grossi (2017)
Abstract Background and objectives There is a strong demand for fast and predictable anesthesia recovery with few side effects. Choice of the hypnotic agent could impact on that. This study investigated the differences between recoveries after remifentanil-propofol and remifentanil-desflurane anesthesias guided by bispectral index (BIS®). Methods Forty patients were randomly assigned into 2 groups according to the anesthesia technique applied: remifentanil-propofol (REM-PRO) and remifentanil-desflurane (REM-DES). After the discontinuation of the anesthetics, the times to extubation, to obey commands and to recover the airway protection reflex were recorted. In the post-anesthetic recovery room (PACU) it was recorded the occurrence of nausea and vomiting (PONV), scores of Ramsay sedation scale and of numeric pain scale (NPS), morphine dose and length of stay in the unit. Results Data from 38 patients were analyzed: 18 from REM-PRO and 20 from REM-DES group. Anesthesia times were similar (REM-PRO = 193 min, SD 79.9 vs. 175.7 min, SD 87.9 REM-DES; p = 0.5). REM-DES had shorter times than REM-PRO group: time to follow command (8.5 min; SD 3.0 vs. 5.6 min; SD 2.5; p = 0.0) and extubation time (6.2 min; 3.1-8.5 vs. 9.5 min; 4.9-14.4; p = 0.0). Times to recover airway protective reflex were similar: 16 patients from REM-PRO (88.9%) restored the airway protective reflex 2 min after extubation vs. 17 from REM-DES (89.5%); and 2 patients from REM-PRO (11.1%) vs. 2 from REM-DES (10.5%) 6 min after extubation, p = 1. Ramsay sedation score, NPS, PONV incidents, morphine dose and PACU stay of length PACU were also similar. Conclusion Remifentanil-desflurane-based anesthesia has a faster extubation time and to follow command than remifentanil-propofol-based anesthesia when both guided by BIS®.